WE ARE THE BORG: Is the convergence of human and machine really upon us? - Kean, Sam (American Scholar)
The article discusses Ray Kurzweil's book, "The Singularity Is Nearer," which explores the convergence of human and machine intelligence. Kurzweil predicts that by the late 2030s, humans will be able to link their brains to computers and achieve nonbiological thinking. However, the author raises doubts about the feasibility of this vision, pointing out the limitations of current AI technology and the challenges of replicating human cognition. The article also highlights Kurzweil's ideas about transforming industries and using AI for drug discovery, but questions the practicality of these concepts. Overall, the article presents a critical perspective on Kurzweil's predictions while acknowledging the potential for future advancements.